154. Retrospective review of pre-treatment QA VMAT plans using the COMPASS® system. (December 2018) - Piergentili, M.; Zefiro, D.; Rambaldi Guidasci, G.; Scolaro, T.; Foppiano, F.
Abstract : Purpose: This study retrospectively reviewed about 170 pre-treatment QA VMAT plans. This was performed via quantifying the agreement between treatment planning system (TPS) calculations and reconstructed dose distributions from measurements, based on absolute dose comparisons (3% tolerance for average dose to the PTV) and global gamma index assessment (3%/3 mm criterion). Methods: 14 cerebral, 38 H&N, 18 lung, 4 breast, 53 prostate, 26 pelvis and other 16 VMAT plans were optimized and calculated with Elekta Monaco 5.11 TPS to be delivered on an Elekta Synergy LINAC equipped with Agility MLC. Pre-treatment patient specific quality assurance was performed using a 2D-array of ionization detectors (MatriXX Evolution with gantry angle sensor). Dose distributions and DVHs were reconstructed with COMPASS® (v.4, IBA Dosimetry). Results: With respect to the PTV average dose differences, it was found that all the pelvis plans fell within the 3% tolerance and 85% point with γ < 1 . About 97% of H&N plans fell within the 3% tolerance and 85% point with γ < 1 if the TPS calculation was made in water. In H&N plans, the mean percentage of points with γ > 1 is 11.6 ± 7.5 and 6.7 ± 4.9 if dose was calculated in medium or water, respectively (COMPASS always calculate dose in water). We additionally analyzed the discrepancies of the D1 to the spinal cord, the D mean to the parotids in the H&N and D mean to the bladder and rectum in the prostate cases. All the statistics are presented in Table 1. Conclusions: It was not found any correlation between the γ analysis and MU or the number of segment of the treatment plans. Prostate and pelvis plans show the best agreement in the comparison between TPS and measurements with COMPASS. New limits and methods of comparison are under investigation for the other anatomical districts.